2005
DOI: 10.1002/maco.200403855
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of galvanic corrosion of magnesium coupled to a steel fastener in NaCl solution

Abstract: The galvanic corrosion of magnesium alloy AZ91D coupled to a steel fastener was studied using a boundary element method (BEM) model and experimental measurements. The BEM model used the measured polarization curves as boundary conditions. The experimental program involved measuring the total corrosion rate as a function of distance from the interface of the magnesium in the form of a sheet containing a mild steel circular insert (5 to 30 mm in diameter). The measured total corrosion rate was interpreted as due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 17 publications
2
56
0
Order By: Relevance
“…In addition, such simulations have the longterm potential to predict critical aspects of the corrosion behavior of galvanically coupled Mg. 13,14,24,25 Jia et al used the Boundary Element Method (BEM) to calculate the corrosion rate of a galvanically coupled Mg alloy with use of a measured polarization curve, and compared the calculated results with their experimental measurements. 13,14 Overall, they observed that the model adequately predicted the corrosion distribution for different anode-to-cathode area ratios and electrolyte thicknesses.14 However, in some instances the model was observed to underpredict the experimental dissolution rate by more than 50%.13 They interpreted the underprediction as the evidence for selfcorrosion, which they estimated to be up to 230 mm/year. …”
mentioning
confidence: 99%
“…In addition, such simulations have the longterm potential to predict critical aspects of the corrosion behavior of galvanically coupled Mg. 13,14,24,25 Jia et al used the Boundary Element Method (BEM) to calculate the corrosion rate of a galvanically coupled Mg alloy with use of a measured polarization curve, and compared the calculated results with their experimental measurements. 13,14 Overall, they observed that the model adequately predicted the corrosion distribution for different anode-to-cathode area ratios and electrolyte thicknesses.14 However, in some instances the model was observed to underpredict the experimental dissolution rate by more than 50%.13 They interpreted the underprediction as the evidence for selfcorrosion, which they estimated to be up to 230 mm/year. …”
mentioning
confidence: 99%
“…Importantly, the VPD observed was an effective indicator of how corrosion developed due to microstructural features. Subsequent to these findings, several research groups [31][32][33][34][35][36][37][38][39] have been able to verify that SKPFM is both reliable and effective in characterizing various alloy systems to accurately explain corrosion initiation behavior.…”
Section: Discussionmentioning
confidence: 95%
“…A better compatibility in salt water environment exhibit steel fasteners with zinc or tin-zinc coatings, however they also experience corrosion due to the coating porosity. During performance simulation of mild steel fastener to AZ91 cast alloy in 5% NaCl solution, two corrosion mechanisms active in area from 1 to 2 cm from the interface were identified: galvanic corrosion and self corrosion (Jia et al, 2005). It was confirmed that the microgalvanic cells exist on the surface of AZ91D alloy which have potential differences of the order of 100 mV between alloy phases: matrix of α-Mg and Mg 17 Al 12 intermetallics.…”
Section: Threaded Fastenersmentioning
confidence: 85%